Desenvolvimento de populações interespecíficas de trigo para a resistência à giberela - Frizon, Patrícia (2019)
Fusarium Head Blight, mainly caused by Fusarium graminearum Schwabe [telomorphs: Gibberella zeae Schwein. (Petch) is one of the most destructive diseases of wheat, both in Triticum aestivum L. and in T. durum L. The infected grain is generally contaminated with mycotoxins that pose risks to human and animal health because it is highly toxic. The challenge in the genetic improvement of plants aiming resistance to giberela is to combine this characteristic with agronomic aspects and of superior quality, such as grain yield and nutritional quality. Exotic species, similar to wheat, are used in hybridizations for fungus resistance. Success depends on the genes that will be introgressed, either through backcrossing or direct intersections. In the present study, commercial wheat cultivars BRS Guamirim and BRS 179, both of high grain yield and moderate resistance to giberela, were crossed with three accessions of synthetic wheats (CIGM90.909, CIGM92.1666 and CIGM90.93.298). previously characterized with moderate resistance to giberela, generating F2 progenies and followed by backcrosses and RC2. The progenies derived from these backcrosses were sown in a "giberela nursery" with four replications, allowing to verify the real severity of the spikes, incidence of giberela in the grains, yield and agronomic traits. In addition, the meiotic behavior of all progenies and pollen viability were analyzed in order to estimate the genetic stability. Some segregant populations presented lower severity and percentage of gibberellated disease grains in the field evaluations, such as the CIGM90.909 / BRS 179 cross. The best resistance II and III were also observed in this access. However, in this population it was obtained lower yield of grains per plant. All populations from crosses with the BRS 179 parent showed better results for disease resistance. All populations had a meiotic index above 90%. Pollen viability was also stable. The CIGM90.909 / BRS Guamirim population had higher yield and smaller size of pollen grains, while CIGM90.909 / BRS 179, which obtained the lowest yield of grains per plant had larger pollen sizes. The selection of the population and its progeny is often seen as a decisive process because if the average level of resistance is insufficient, the population is discarded. These results indicate that it may be possible to identify and select segregating lines that combine resistance to giberela, superior agronomic performance and genetic stability